Šiaurės žemaičių intervokalinių priebalsių trukmė - Kliukienė, Regina (Kalbotyra, 1995)
Acoustic analysis of the length of the consonants in the Northern Žemaitian dialect has shown that: a) the length regularities are common to the Northern Žemaitian and Standard Lithuanian; b) the length of the consonants is determined by the activity or passivity of vocal cords at the time of articulation; c) the length is very closely correlated with the manner of articulation; d) the place of articulation and the softness or hardness do not have any noticeable effect on the length of the consonants.